Medeu sports complex: A representation of the image philosophy in Kazakhstan - A., Tolegen; Koshenov K., Assylkhanov Y.,; A., Sabirova (Opción, 2020)
This paper has an objective to reveal and analyze the stages of development of Medeu sports complex. Medeu is a high-mountain skating rink located in Almaty, Kazakhstan, East Asia. It is a venue for worldwide international competitions in ice-skating. The article studies the impact of different time periods on the stadium functioning, its history of changes. The problems that occurred during the operation of sports complex, as well as future prospects for its functioning are observed. In order to implement the specified objective, various methods and principles of research study were applied.